2008
DOI: 10.1007/s10495-008-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic resistance exhibited by dexamethasone-resistant murine 7TD1 cells is controlled independently of interleukin-6 triggered signaling

Abstract: Interleukin-6 (IL6)-mediated signaling is known to play a role in pathogenesis and resistance in several cancers like multiple myeloma (MM). In this report we used the IL6-dependent 7TD1 murine B-cell hybridoma as an in vitro model to study the interactions between IL6-signaling pathways and the development of dexamethasone resistance. Though in initial stages, 7TD1 cells grew IL6-dependent and were sensitive to dexamethasone-induced apoptosis, chronic exposure to dexamethasone led to a dexamethasone-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Previous studies in our laboratory have established a dexamethasone-resistant 7TD1 sub-line (7TD1-Dxm) and have observed that 7TD1-Dxm cells show IL6 independence for proliferation and dexamethasone resistance concomitantly [15]. We have also shown that dexamethasone resistance observed in 7TD1-Dxm cells is due to inhibition of cytochrome c release [16].…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Previous studies in our laboratory have established a dexamethasone-resistant 7TD1 sub-line (7TD1-Dxm) and have observed that 7TD1-Dxm cells show IL6 independence for proliferation and dexamethasone resistance concomitantly [15]. We have also shown that dexamethasone resistance observed in 7TD1-Dxm cells is due to inhibition of cytochrome c release [16].…”
Section: Introductionmentioning
confidence: 56%
“…7TD1-Dxm (Dexamethasone-resistant 7TD1) cells were generated as described previously [15]- [19]. Both 7TD1 and 7TD1-Dxm cells were cultured and maintained in complete culture medium as noted previously [15]- [19].…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations